Perancangan Rute Pengiriman pada PT. ABC untuk Meminimasi Tingkat Keterlambatan Pengiriman dan Biaya Transportasi Menggunakan Model Mixed Integer Linear Programming - Putri, Aliya Mahmuda; Ardiansyah, Muhammad Nashir; Chulasoh, Budi Santosa (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
The distribution of vegetables in Indonesia is still constrained by the guarantee of continuity between product quality, the minimum amount of supply, and the timeliness of delivery. Time is a very crucial factor in the distribution of vegetables because vegetables are commodities that experience a rapid decline in quality, so they must reach consumers at the right time. PT ABC is a company engaged in the distribution of fresh fruit and vegetables. The problem faced by PT ABC in distribution activities lies in the delay in delivery. This delay problem can be minimized by optimizing the distribution network so that delivery delays do not occur again. The characteristic of the problem contained in this final project is Vehicle Routing Problem with Heterogeneous Fleet and Time Window. The model that will be used to solve this problem is the Mixed Integer Linear Programming model with the main objective to minimize transportation costs and minimize delivery delays. Problem solving was carried out using the Python programming language and Gurobi Solve. The final result obtained is a reduction in the percentage of delays by 5% and a minimization of transportation costs by 4%.